(untitled) (Salud, Arte y Cuidado, 2021)
The present study aims to analyze the clinical and epidemiological characteristics of neonatal sepsis Polyvalent Intensive Care Unit, AgustínZubillaga Pediatric University Hospital, Barquisimeto, Lara State. Regarding the research methodology, it presents a quantitative, descriptive, non-experimental, cross-sectional and retrospective approach, in which newborns between 0 to 28 days old who present the diagnosis were taken as the histories of the population. of neonatal sepsis, the results found in the histories of the clinical characteristics of neonatal sepsis, the transmission mechanism was 84% ​​vertical, 16% nosocomial, the time of presentation 84% early and 16% late, a blood culture was performed at 86 % and only 14% were positive and 71% isolated gram negative bacteria and 29% gram positive, the germs isolated in the cultures are gram negative bacteria and those with the highest incidence where 7% were for Echericha coli and another 7% were for Klebsiellapneumoniae, positive reports for 0% beta group streptococci. Complications of sepsis presented by the patients were; respiratory distress 100%, vomiting 27%, seizures 58% and hypotonia 53%. Patients presented signs of sepsis 51% reticulated skin, 26% slow capillary filling, 21% irritability, 47% abdominal distention, 9% hepatomegaly, 35% apnea , 21% tense fontanelle, 58% jaundice, 49% hypothermia, 53% hypotonia, 86% skin paleness, 19% weak pulses, and 51% cyanosis. The epidemiological characteristics highlight the neonatal data: female 56%, male 44%, with a preterm gestational age 53% at term 44% and post-term 3%, while the maternal data the maternal age was comprised of 12 to 19 years 23%, from 20 to 35 years old and 67% and over 35 years old 9%. The conclusions were that sepsis with clinical complications such as respiratory distress, vomiting, seizures and hypotonia continues to be a frequent pathology in neonatology with a significant percentage of morbidity and mortality.